Modelling consumer's behaviour of the meat consumption in Slovakia - Renata BENDA PROKEINOVA; Martina HANOVA (Agricultural Economics (AGRICECON), 2016)
There exists a plenty extensive theoretical and empirical literature on what determines the consumption levels over time and across countries, but less research into the changes in the consumption patterns (i.e. the mix of different goods and services that is purchased). To better understand how changing incomes and prices influenced the consumption patterns, the contribution estimates the Almost Ideal Demand System (AIDS) models. The aim of the paper is to find patterns and preference changes in the consumer demand for meat in Slovakia. From the methodological aspect, there were used important items of the demand, and for the consumer behaviour analysis, there were computed elasticity coefficients by using the model AIDS. The coefficients of the price and income demand elasticity were determined. The computed elasticities showed that all meat items had a positive income elasticity of demand which implies that they were normal goods. Beef and pork were expenditure (income) elastic and hence could be considered as a luxury, while poultry and fish were income inelastic meaning that those were of necessity.